Analysis of Stock Mutual Fund Performance Measurement and Comparison with LQ-45 Index - Kartika Adiputra; I Made Pande Dwiana Putra (Quantitative Economics and Management Studies, 2024)
Evaluation of performance is one of the important things that must be considered when choosing the type of mutual fund for investment purposes. Performance measurement is needed to help investors determine their mutual fund choices according to the return and risk of each instrument. Mutual fund performance measurement is not only measured by Net Asset Value (NAV) or returns, but also by comparison with market performance against certain benchmarks. The use of benchmarks in measuring mutual funds is intended to compare whether mutual fund performance can beat the market or lose to the market. This research compares the performance of 32 active stock mutual funds determined using a purposive sampling method with the performance of the LQ-45 index. The measurement method used is the Sharpe and Treynor method. The research hypothesis was tested using the Mann – Whitney Test with the SPSS version 16 program. The research results showed that the 32 stock mutual funds studied had better performance than the LQ-45 index performance measured using both the Sharpe method and the Treynor method. The stock mutual fund that has the highest Sharpe value is the Simas Stock Featured Mutual Fund with a Sharpe index of 0.2148, while the lowest is the Schroder Dana Achievement Plus Mutual Fund with an index value of -1.3655. The stock mutual fund that has the highest Treynor value is the Mandiri Investa Smart Bangsa Mutual Fund with a Treynor index of 0.0653, and the lowest is the Dana Ekuitas Prima Mutual Fund with a Treynor index of -0.6655.